Impact of ethnic closeness and socio-economic status of migrants on the empathy of domicile population in Serbia - Kidžin, Nemanja (Sociološki pregled, 2024)
The goal of this research is to examine the factors that influence the empathic reactions of the local Serbian population toward migrants. The variance analysis has indicated differences in the perception between refugees from the Middle East, who evoke the lowest empathy, and refugees from Eastern Europe, who evoke the greatest empathy. Ethnicity has proved to be significant in discrimination against migrants, unlike the socio-economic factor, but the interaction between these two factors had marginal significance. In addition to these findings, the influence of the context has also been established. The respondents do not differentiate between groups when discrimination occurs, and they show empathy towards all migrants in distress, but if migrants receive certain forms of assistance, preferences arise towards ethnically closer groups with a lower socioeconomic status.